New echocardiographic indices of shift to biventricular failure to optimize risk stratification of chronic heart failure. (7th December 2021) - Mandoli, Giulia Elena; Pastore, Maria Concetta; Benfari, Giovanni; Setti, Martina; Nistor, Dan; D'Ascenzi, Flavio; Focardi, Marta; Baccani, Bernardo; Patti, Giuseppe; Valente, Serafina; Mondillo, Sergio; Cameli, Matteo
Abstract: Aims: The present study investigated the prognostic impact of either isolated left atrial (LA) impairment, or its association with right ventricular (RV) failure, in heart failure (HF) with reduced ejection fraction (HFrEF), using basic and speckle tracking echocardiography (STE). Methods and results: One hundred and six outpatients with HFrEF were enrolled in this prospective observational study. Patients with primary lung diseases, non‐sinus rhythm, previous cardiac surgery, and poor acoustic window were excluded. After clinical examination and basic echocardiography, STE was used to measure peak atrial longitudinal strain (PALS) and a new marker of RV performance and pulmonary circulation relation: free‐wall RV longitudinal strain (fwRVLS)/systolic pulmonary artery pressure (sPAP). Patients were followed for all‐cause/cardiovascular death and HF hospitalization. Of 84 eligible patients (60.1 ± 11.5 years; 82% male patients), 48 reached the combined endpoint (cardiovascular death and/or HF hospitalization). Population was divided into three groups: Group 1 (PALS ≥ 15 and fwRVLS/sPAP ≤ −0.5), Group 2 (PALS ≤ 15 and fwRVLS/sPAP ≤ −0.5), and Group 3 (PALS ≤ 15 and fwRVLS/sPAP > −0.5). Mean follow up was 3.5 ± 0.3 years. The higher severity groups were associated with higher LA volume index ( P  < 0.0001), New York Heart Association class ( P  = 0.02), mitral regurgitation ( P  = 0.0004) and tricuspid regurgitation grades ( P  < 0.0001), lower left ventricular (LV) ejection fraction ( P  = 0.0003), LV global longitudinal strain ( P  < 0.0001), PALS ( P  < 0.0001), tricuspid annular plane systolic excursion ( P  < 0.007), sPAP ( P  < 0.0001), and RV strain ( P  < 0.0001). Reduced PALS and fwRVLS/sPAP were independent predictors of the combined endpoint with adjusted Cox models (hazard ratio = 9.54; 95% confidence interval = 2.95–30.92; P  = 0.0002 for Group 3 vs. Group 1). Kaplan–Meier curves showed early and persistent divergence between the three groups for the prediction of the combined endpoint and of all‐cause death ( P  < 0.0001). Conclusions: The combination of LA and right heart damage entails worse prognosis in patients with HFrEF. The evaluation of PALS and fwRVLS/sPAP could aid risk stratification of HFrEF patients to provide them early treatment.